(untitled) (Indian Journal of Animal Production and Management, 2014)
The investigation was carried out on-farm, in the Pabuda village of Sirohi block in Sirohi District Rajasthan, located in the native tract of Sirohi Goats. In order to study the effect of supplementation of concentrates, 30 male kids were randomly divided into three equal groups and kept either on normal browsing (as per farmer’s practices); (G1) with additional supplementation of concentrate mixture at 100 (G2) and 150 (G3) g per day per kid. During the experiment period of 120 days, BW of kids was recorded fortnightly. The average daily gain (ADG) of the kids was 31.32+ 0.47, 54.02+0.11 and 62.84+ 0.37 in G1, G2 and G3 respectively with significant differences(P<0.05) among all the groups. It is concluded that, provision of 150g concentrate mixture significantly improved growth performance of Sirohi male kids attributable to a more efficient utilization of the native pasture.